Anti-diabetic activity and microbial quality of ready-to-serve Momordica charantia (MC) drink - Chern, Pei Ern; Mahyudin, Nor Ainy; Ghazali, Hazrina; Mahmud @ Ab Rashid, Nor Khaizura (Universiti Putra Malaysia Press, 2017)
Diabetes mellitus has a high prevalence in Malaysia and is expected to rise in the future due to lifestyle changes. Thus, consumers are turning to alternative methods in the prevention and cure of the disease. The Momordica charantia has been studied for its anti-diabetic activity both in vitro and in vivo and is shown to be effective in inhibiting glucose absorption. Therefore, the MC is used as a main ingredient in the development of health beverages to offer alternatives for patients or the health conscious. The microbial quality of the product is examined to ensure the safety of the product and to find methods to enhance its shelf life.